Soft Computing: State of the Art Theory and Novel Applications - Yager, Ronald R.; Abbasov, Ali M.; Reformat, Marek Z.; Shahbazova, Shahnaz N. (Studies in Fuzziness and Soft Computing, 2013)
This book is a tribute to Lotfi A. Zadeh, the father of fuzzy logic, on the occasion of his 90th Birthday. The book gathers original scientific contributions written by top scientists and presenting the latest theories, applications and new trends in the fascinating and challenging field of soft computing.